A Comprehensive Study of Ground Measurement and Satellite‐Derived Data of Global and Diffuse Radiation. Issue 3 (5th October 2018) - Mahima,; Karakoti, Indira; Pathak, P. P.; Nandan, Hemwati
Abstract : The comparative study of measured and calculated data of India Meteorological Department (IMD) and National Aeronautics and Space Administration (NASA) for 23 locations of India for 15 years (1986–2000) is presented. Global and diffuse radiation data are used in the study and to make the study comprehensive, three statistical predictors, viz., mean percentage error (MPE), root mean square error (RMSE), and mean bias error (MBE) are used for the comparison. The results show that for global radiation, MPE is maximum of −36.65% for Shillong and minimum of 0.93% for New Delhi. MBE is found to be maximum of 1.63 kWh/m 2 for Shillong while it is minimum (0.04 kWh/m 2 ) for Nagpur. RMSE is maximum (2.14 kWh/m 2 ) for Shillong and minimum for Ranchi (0.19 kWh/m 2 ). For diffuse radiation, MPE is highest for Bhavnagar (100%) and lowest for Hyderabad (81.33%). MBE is maximum of −7.73 kWh/m 2 and minimum of −4.62 kWh/m 2 for Srinagar. RMSE is maximum for Bhavnagar (8.26 kWh/m 2 ) and minimum for Srinagar (4.73 kWh/m 2 ). © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13060, 2019